Application of Mathematics Learning Methods to Students of SMP N 11 Bengkulu - Hidayana, Rizki Apriva; Saputra, Jumadil (International Journal of Ethno-Sciences and Education Research, 2023)
Mathematics is a clear and precise language, quantitative in character, and a method of logical thinking. It significantly impacts the advancement of all branches of science. This study aims to ascertain the instructional strategies used by teachers of SMP N 11 Bengkulu. A descriptive case study was chosen as the research methodology. The participants in this study were three math teachers from SMPN 11 Bengkulu who taught various classes using various teaching resources. Analysis of data using qualitative or non-statistical methods. The lecture and question-and-answer formats were employed to introduce the lesson in light of the findings of the field observations. During the core activities, the question-and-answer, the assignment, the lecture, the discussion, and the demonstration approach are all used. At the end of the lesson, the math teacher employs the lecture technique, question-and-answer method, and assignment method. The assignment and question-and-answer methods are the techniques the teacher uses while evaluating student learning. The technique used in the class results in an average mark that satisfies the academic completeness criteria.